Powierzchnie referencyjne i kontrolne – użyteczne narzędzie dla leśnictwa? - Wójcicki, Adam (Leśne Prace Badawcze, 2017)
In the current age, the increased need for the restoration of forest ecosystems necessitates a better understanding of natural processes. Forest stands that are affected only by natural processes and disturbances can serve as references and controls for comparison with cut or otherwise managed forests. Such a comparison may help us determine, whether our sylvicultural practices actually pursue the goal of sustainable development. It is also important to use uniform terminology across the world to facilitate sharing of experiences and results. Creating reference and control stands in every ecoregion will provide a rich scientific basis for comparison with managed forests and allow us to design and apply restoration methods more effectively.